How High School Students Solve Proportional Reasoning Problem? - Ahmad Zulfa Khotimi; Sufyani Prabawanto; Al Jupri (Universitas Syiah Kuala, 2024)
This research is motivated by the phenomenon of students' difficulties in solving proportional reasoning problems and the lack of proportional reasoning research at the high school level. This research aims to describe in depth the ability of high school students to solve proportional reasoning problems and learning obstacles that may occur. The method used is qualitative with a case study approach. The research subjects involved were 5 students from grades 10 to 12. The instruments used were tests and interview guides. The research results showed that there were 4 mistakes made by students in solving proportional reasoning problems, namely (1) Using the additional strategy in solving proportional reasoning problems; (2) Not being able to solve problems of indirect proportion; (3) Using multiplication strategies in solving non-proportional problems; and (4) Not being able to compare ratios. Concerning learning obstacles, there are 2 types of learning obstacles that are indicated to be experienced by students, namely epistemological obstacles and ontogenic obstacles. The results of this research can be used as a basis for carrying out further research in the form of research that designs learning flows and/or learning designs that can develop students' proportional reasoning abilities.